Substituição da adubação nitrogenada mineral pela cama de frango na sucessão aveia/milho - Santos, Loana Bergamo dos; Castagnara, Deise Dalazen; Bulegon, Lucas Guilherme; Zoz, Tiago [UNESP]; Oliveira, Paulo Sérgio Rabello de; Gonçalves Júnior, Affonso Celso; Neres, Marcela Abbado (My University, 2014)
The constant search for sustainability of production systems have driven research to find alternatives to the problems arising from the intensified use such systems. In this context the present work aimed study the effects of substitution of mineral nitrogen by chicken litter in oat and corn crop in succession and the chemical characteristics of soil. The study was conducted during the period May 2009 to March 2010 in area of Oxisol. The design was of randomized block with four replications. The six treatments were obtained by a combination of different amounts of chicken litter (0, 1500, 3000, 4500, 6000 and 7500 kg ha-1) applied 30 days before the sowing of oats combined with the mineral nitrogen applied in coverage in corn (311.1, 257.8, 202.2, 148.9, 95.6, 42.2 kg ha-1of urea), for the total supply of 140 kg ha-1of nitrogen (N). The application of poultry litter in oat promotes increased the production of dry matter, and content and accumulation of N. The mineral nitrogen substitution by chicken litter increases the yield of corn crop. The use of poultry litter alters the chemical properties of soil, increasing the levels of organic matter, exchangeable Al and acidity potential. However lowers the pH, K, Ca, Mg, sum of bases and base saturation.
Mineral nitrogen substitution by chicken litter in succession oat/corn
Keywords: Avena strigosa; Nitrogen; Organic matter; Zea mays